Draft genome sequence of the novel thermoacidophilic archaeon Acidianus copahuensis strain ALE1, isolated from the Copahue volcanic area in Neuquén, Argentina - Urbieta, María Sofía (2014)
Acidianus copahuensis is a recently characterized thermoacidophilic archaeon isolated from the Copahue volcanic area in Argentina. Here, we present its draft genome sequence, in which we found genes involved in key metabolic pathways for developing under Copahue's extreme environmental conditions, such as sulfur and iron oxidation, carbon fixation, and metal tolerance.